Simulation-based improvement and modification for performances of hospitals: a case study. (22nd June 2021) - Ershadi, Mohammad Mahdi; Shafaeizadeh, Ahmad
It is necessary to improve the process of service provided to patients due to their increased expectations. So, hospital managers need to find current prioritised problems of the hospital and improve them. However, some results of improvement plans are unpredictable due to the complexity of the hospital. Therefore, a simulation model is proposed with a mathematical model and the Taguchi method based on the real data obtained from a hospital in this paper. Besides, FMEA is utilised to find the priority of problems and guide improvement teams. Decreasing resource wastes, the number of patients in the queue, waiting time in different departments, increasing value-added time, utilisation of resources, and productivity are considered in a mathematical model. The best improvement scenarios and their effects are defined using the proposed model in this paper. After the actual implementation of them, the difference between reality and the expected condition was less than 10%.